Desain teknologi pembelajaran untuk meningkatkan efektifitas dan hasil belajar - Abd Ghofur (Journal of diversity in learning (JDIL), 2023)
This study aims to find out how to use learning technology and learning outcomes and whether there is the use of technology as a learning medium to achieve effective learning outcomes. The type of research used is descriptive qualitative research. In this study, the focus of the research was the use of learning technology and learning outcomes in the Economic Education Study Program. The results of the study show that in the Economics Education Study Program, the use of learning technology has had a positive influence on lecturers in designing, implementing, and evaluating learning, but this has not fully had a positive effect on student learning gains. especially in the affective and psychomotor domains, while the influence of the use of learning technology has a positive impact on the cognitive domain of students.